Case Study : Siti Khadijah Apparel Sdn Bhd / Nursyuhada Bakhari - Bakhari, Nursyuhada (2021)
Siti Khadijah Apparel Sdn. Bhd started their business with a determination from their owner Puan Padzilah Enda Sulaiman (“Padzilah”) in helping people to have a comfortable telekung in order for them to complete their prayer comfortably. It is because, she had encountered a situation where she did not fully satistified with a telekung that she bought due to inefficient design that made her not comfortable wearing it. Therefore, they encourage herself to sewed the telekung herself and up until today, she had managed to have her own brand for telekung which is Siti Khadijah with trademark “Lambang Cinta Abadi”. Siti Khadijah Apparel had managed to have more than just a telekung in their product range. They also managed to have their own loyal customers. In fact, Siti Khadijah Apparel has developed and grown into a well known telekung brand in Malaysia. From this case study, I analysed the strength, weaknesses, opportunity and threats of the company through SWOT Analysis as a tool to study their successful. Thus, these alternatives can be practiced by the owner to strengthen their management and overcome their company’s problem.